Assessing the factors affecting the formation of entrepreneurial opportunities in rural areas; Case study: Behbahan County - sara ferdosi; hasanali faraji sabokbar; alireza darbaneh astaneh; fazileh khani (تحقیقات کاربردی علوم جغرافیایی)
The development of sustainable entrepreneurship plays a critical role in promoting human well-being and environmental preservation. To achieve this objective, it is essential to understand the factors affecting the emergence of entrepreneurial opportunities in different regions. Therefore, this study aims to explore these factors through a descriptive-analytical survey, with data collected from documentary research and field surveys. The number of experts was 52 who were purposefully sampled using the snowball method. The study employed four indicators and 28 items, which were measured using the Likert scale. A sample of 439 individuals, consisting of 387 villagers and 52 experts, participated in the study. The selection of the 387 villagers was determined using Cochran's formula from a statistical population of 215,104 people. Descriptive statistics, such as mean and standard deviation, as well as inferential statistics, including one-sample t-test and one-way analysis of variance, were used to analyze the data. The results of the one-sample t-test revealed that all indicators examined in the study were statistically significant at a confidence level above 95%. These findings suggest that the villagers' perception of these indicators is positive, given that the observed mean value (3.1) is assumed to be positive. Furthermore, the evaluation statistics, such as the multiple determination coefficient and adjusted coefficient of determination, indicated that the transcendental model provides a better understanding of the factors influencing entrepreneurial opportunities and the key areas of entrepreneurship. The analysis of the transcendental model demonstrated that government subsidies, investment and facilities, product insurance, and education are the most influential factors in the formation of entrepreneurial opportunities. Additionally, the most important sectors for creating and developing entrepreneurship were found to be handicrafts, home-based jobs, oil and gas, medicinal plants, and date production. Overall, the results highlight the region's significant potential for natural, economic, and industrial entrepreneurship, emphasizing the necessity for the government to prioritize investment in entrepreneurship.